Foraging behaviour alters with social environment in a juvenile songbird. Issue 1939 (25th November 2020) - Franks, Victoria R.; Ewen, John G.; McCready, Mhairi; Thorogood, Rose
Abstract : Early independence from parents is a critical period where social information acquired vertically may become outdated, or conflict with new information. However, across natural populations, it is unclear if newly independent young persist in using information from parents, or if group-level effects of conformity override previous behaviours. Here, we test if wild juvenile hihi ( Notiomystis cincta, a New Zealand passerine) retain a foraging behaviour from parents, or if they change in response to the behaviour of peers. We provided feeding stations to parents during chick-rearing to seed alternative access routes, and then tracked their offspring's behaviour. Once independent, juveniles formed mixed-treatment social groups, where they did not retain preferences from their time with parents. Instead, juvenile groups converged over time to use one access route per group, and juveniles that moved between groups switched to copy the locally favoured option. Juvenile hihi did not copy specific individuals, even if they were more familiar with the preceding bird. Our study shows that early social experiences with parents affect initial foraging decisions, but social environments encountered later on can update transmission of arbitrary behaviours. This suggests that conformity may be widespread in animal groups, with potential cultural, ecological and evolutionary consequences.